Pengaruh Kualitas Sumber Daya Manusia dan Kepuasan Masyarakat terhadap Kinerja Pegawai pada Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Batang Hari - AZ, Siti Marlina; Ratna, Ratna; Delima, Rts Hartha (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of human resource quality and public satisfaction on employee performance at the Population and Civil Registration Office of Batang Hari Regency, totaling 57 employees who are also the sample in this study. The approach used is a quantitative descriptive approach, while data collection uses a questionnaire with a Likert scale. Data analysis uses multiple linear regression. The results of this study found that simultaneously and partially there is a positive and significant influence between the variables of human resource quality and public satisfaction on employee performance at the Population and Civil Registration Office of Batang Hari Regency.